IMPLEMENTASI TEKNOLOGI PEMBELAJARAN KAHOOT GEMBIRA SOLUSI PEMBELAJARAN JARAK JAUH - Lucia Prabawati Prasetyaningsih (Universitas PGRI Palembang, 2021)
The prolonged pandemic period requires students to accept the fact that they cannot attend school for face-to-face learning as usual. The implementation of distance learning (PJJ), although on the one hand it is considered to have advantages, because it is able to provide solutions to the world of education during this pandemic, it has many weaknesses. The more time students participate in Distance Learning, the more it is felt that the feeling of boredom is increasingly felt by students. Learning also feels less effective. Facing this situation, SDN 01 Kulu Pekalongan Regency, is trying to find a new breakthrough as a solution in Distance Learning which is named